Artificial Intelligence‐Based Clinical Decision Support for COVID‐19–Where Art Thou?. (23rd June 2020) - Unberath, Mathias; Ghobadi, Kimia; Levin, Scott; Hinson, Jeremiah; Hager, Gregory D.
Abstract : The COVID‐19 crisis has brought about new clinical questions, new workflows, and accelerated distributed healthcare needs. Although artificial intelligence (AI)‐based clinical decision support seemed to have matured, the application of AI‐based tools for COVID‐19 has been limited to date. In this perspective piece, the opportunities and requirements for AI‐based clinical decision support systems are identified and challenges that impact "AI readiness" for rapidly emergent healthcare challenges are highlighted. Abstract : The COVID‐19 crisis has brought about new clinical questions, workflows, and accelerated healthcare needs. While artificial intelligence (AI)‐based clinical decision support seemed to have matured, the application of learning‐based tools for COVID‐19 has been limited to date. This essay identifies opportunities and requirements for AI‐based decision support systems and highlights challenges that impact "AI readiness" for rapidly emergent healthcare challenges.